2022
DOI: 10.1177/09673911221108742
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of thiolated chitosan based biodegradable nanoparticles of ticagrelor and their pharmacokinetics

Abstract: The current study was aimed to design a thiolated chitosan (TC) based mucoadhesive nanoparticle (NP) formulation for enhancing the oral bioavailability of an anti-coagulant, Ticagrelor (TG). Nanoparticles (NPs) containing naturally occurring biodegradable polymers have been revealed as promising carriers for the controlled delivery of various therapeutic agents through the oral route. Ionic gelation technique was adopted to prepare thiolated chitosan nanoparticles of TG (TCNPs/TG) and chitosan (CH) nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Our one step thiolation reaction yielded 787 µmol of thiol groups present per Gram of polymer. These results are in line with findings of who reported that thiolation of chitosan yielded 465 μmol/G of polymer (Shahid et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Our one step thiolation reaction yielded 787 µmol of thiol groups present per Gram of polymer. These results are in line with findings of who reported that thiolation of chitosan yielded 465 μmol/G of polymer (Shahid et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…This interaction ultimately resulted in the preparation of highly entrapped drug nanoparticles. In a previous study conducted by Shahid et al, they prepared ticagrelor-loaded simple chitosan and ticagrelor-loaded thiolated chitosan nanoparticles and reported EE values of 84.1% and 94.3%, respectively [ 39 ]. In another study, Bo Fan et al reported an EE of 98% in thiolated chitosan nanoparticles [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peculiar peaks at 1105.23 and 1055.08 cm –1 suggested −C–O stretching vibrations. 22c 36 The presence of nearly unchanged peaks of TGR at 3409.25, 3289.70, 2910.63, 1611.55, 1532.47, 1441.81, 1200.70, and 1050.25 cm –1 in the drug-loaded nanogels confirm that there was no chemical interaction among drugs and excipients, and the drug was efficiently loaded in the synthesized nanogels. Our findings showed consensus with results previously described by Maria et al, who designed a copolymeric hydrogel by using gelatin, PVA, and AMPS for prolonged sitagliptin and metformin release.…”
Section: Resultsmentioning
confidence: 67%